Not only in cities : creative activities in rural areas with a case study of Lower Silesia - Janc, Krzysztof; Raczyk, Andrzej; Dołzbłasz, Sylwia (De Gruyter, 2020)
The objective of the present study is to identify rules governing the distribution and thematic structure of creative activities, using the region of Lower Silesia in southwestern Poland as an example. This empirical study is based on the data obtained from the Central Registration and Information on Business (CEIDG) as of 2018. Rural areas (compared to cities) generally display a lower level of economic activity. Analysis results confirm that craft-based activities are usually carried out outside large cities. A clear structure of specialisation among creative activities indicates that rural areas should mainly undertake activities that are consistent with the character of a particular local setting and are strongly connected with local conditions.
Keywords: rural areas; rural development; creativity; Lower Silesia